1990
DOI: 10.1116/1.576417
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy of scanning tunneling tips

Abstract: The resolution of an scanning tunneling microscope (STM) when used for topographic measurement is mainly limited by the shape of the tip. We here report on the shape and structure of tips observed with high resolution electron microscopy before and after the use in a STM. Tungsten tips made by electropolishing and Pt–Ir tips made by electropolishing, cutting, and ion milling are studied. During electropolishing, the tungsten tips easily get covered with a rather thick, unwanted contamination and/or oxide layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Characterization by atomic force microscopy (AFM) showed that this etching treatment produced a smooth surface with typical roughness of 3 to 10 nm. It is highly likely that a thin oxide film forms on the electrochemically etched surface of tungsten [17]; such surface oxide layers can affect the results of nanoindentation tests [18]. In addition,…”
mentioning
confidence: 99%
“…Characterization by atomic force microscopy (AFM) showed that this etching treatment produced a smooth surface with typical roughness of 3 to 10 nm. It is highly likely that a thin oxide film forms on the electrochemically etched surface of tungsten [17]; such surface oxide layers can affect the results of nanoindentation tests [18]. In addition,…”
mentioning
confidence: 99%
“…Furthermore, the reaction at the anode involves the formation of bubbles, which is not mentioned in the reaction above. The formation of an oxide layer during electrochemical etching is discussed in several papers [99,112,113], though none of them really concludes on the dependency of its thickness on the applied external parameters like the bias voltage, current density, OH − concentration etc.…”
Section: Tungsten Tipsmentioning
confidence: 99%
“…Huge number of works on the fabrication of sharp tips have been performed and several techniques have been developed, such as grinding [2,12], cutting [13][14][15][16], mechanical pulling [17][18][19][20][21][22][23][24][25][26][27], chemical or electrochemical etching , field evaporation or other field-induced methods [72][73][74][75][76], beam deposition [77][78][79][80][81][82][83], ion milling [15,[84][85][86][87][88][89][90][91][92][93][94], and others [95].…”
Section: Introductionmentioning
confidence: 99%